TANGGUNG JAWAB PENYELENGGARA SISTEM ELEKTRONIKDALAM MENJAMIN KEMASAN PRODUK PANGAN OLAHAN SAATPENGIRIMAN - Fernando Satria (2021)
The covid pandemic has made changes, one of which is in online food delivery services. The purpose of this paper is to examine how the responsibility of the electronic system operator is to guarantee the packaging of processed food products during online delivery. This study aims to answer the formulation of the problem as follows: the first is how the responsibility of the electronic system operator is to guarantee the condition of the packaging of processed food products according to BPOM Regulation No. 8 of 2020 concerning Control of Drugs and Food Circulated Online, The second is how the electronic system operator responds to the BPOM Regulation number 8 of 2020?. This study uses a juridical normative legal research method with a statute approach approach and interview. The results of the study concluded that: That the Electronic System Operators in responding to BPOM Regulation No. 8 of 2020 have not fully fulfilled what was conveyed by BPOM Regulation No. 8 of 2020, this is evidenced that the drivers are not aware of the existence of BPOM Regulation No. 8 which is used as a guideline in delivering processed food. This lack of socialization from Electronic System Operator. Key words : Responsibilities, Electronic System Operators, BPOM Regulation No. 8 of 2020